Pengaruh Leverage, Profitabilitas, dan Ukuran Perusahaan Terhadap Ketepatan Waktu Pelaporan Keuangan Pada Perusahaan Investasi Yang Terdaftar Di Bursa Efek Indonesia Tahun 2015-2019 - Ferry Kurniawan; Tituk Diah Widajantie (Universitas Sains dan Teknologi Komputer, 2021)
The research goals to obtain information and empirical evidence of the influence of factors that affect the timeliness of corporate financial reporting. The variables used in this study are the leverage, profitability, and company size as independent variables, while the timeliness of financial reporting as the dependent variable. The population in this study are investment sub-sector companies listed on the Indonesia Stock Exchange 2015-2019. This study uses secondary data obtained from www.idx.co.id and related company websites. The data taken is company data for the period 2015-2019 with the sample determination criteria, namely non-probability sampling using purposive sampling technique, in order to obtain 11 sample companies. The analysis technique used in this research is multiple linear regression analysis using SPSS 23 software. The results show that leverage has no effect on the timeliness of financial reporting, as well as profitability and firm size that do not affect the timeliness of reporting finance